A phenylacetaldehyde–flavonoid adduct, 8-C-(E-phenylethenyl)-norartocarpetin, exhibits intrinsic apoptosis and MAPK pathways-related anticancer potential on HepG2, SMMC-7721 and QGY-7703. (15th April 2016) - Zheng, Zong-Ping; Yan, Yan; Xia, Ji; Zhang, Shuang; Wang, Mingfu; Chen, Jie; Xu, Yang
Highlights: Three flavonoids could inhibit PhIP formation in roast beef patties. Six flavonoid–phenylacetaldehyde adducts were detected by UPLC–MS. The structures of six adducts were confirmed by NMR and ESI data. The adductNARA1 was found to significantly induce cancer cell death. NARA1 has anticancer activity via intrinsic caspase, cell context-dependent MAPKs pathways. Abstract: Norartocarpetin, quercetin and naringenin were found to effectively inhibit 2-amino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (PhIP) formation through trapping its phenylacetaldehyde and form their adducts in roast beef patties. Six adducts [8- C - or 6- C -( E -phenylethenyl) flavonoids] formed between phenylacetaldehyde and three flavonoids were detected in roast beef patties by UPLC–MS analyses and compared with their synthetic references. These flavonoid–phenylacetaldehyde adducts were synthesised and further subjected to cytotoxicity tests on three liver cancer cell lines HepG2, SMMC-7721 and QGY-7703. The adduct 8- C -( E -phenylethenyl)norartocarpetin (NARA1 ) was found to significantly induce cancer cell death with IC 50 values about 7 μM. After pre-treating with MAPK and caspase inhibitors, alteration of the cell morphology and cleaved-PARP were detected in liver cancer cell lines administered withNARA1 . These data indicated that norartocarpetin could inhibit PhIP formation in roast beef patties and form norartocarpetin–phenylacetaldehyde adducts. The adductNARA1 has anticancer potential via intrinsic caspase-dependent and cell context-dependent MAPKs pathways.